Evaluation of Knowledge, Awareness, and Attitude Towards Management of Displaced Tooth from Socket (Avulsion) Amongst Nursing Fraternity in Mangaluru City: A Cross-Sectional Study - Shenoy, Prithi; Rao, Ajay; Sargod, Sharan; Suvarna, Reshma; Shabbir, Afreen; Mahaveeran, Shrivya Saloni; Manu, Parvathy; Deepanjan, Manisha (Journal of Health and Allied Sciences NU, 2024)
Introduction The aim of this study was to evaluate knowledge, awareness, and attitude in the management of displaced tooth from socket (avulsion) amongst nursing fraternity in Mangaluru City.Materials and Methods A 20-item questionnaire regarding knowledge, awareness toward management of avulsed tooth was administered to 150 nursing interns.Results Among 150 participants, 47% demonstrated awareness of the storage media for an avulsed tooth. About half of the respondents did not know regarding handling of avulsed tooth. The majority of participants responded positively about attending workshop on dental trauma management.Conclusion Given the frequent encounter with emergencies, it is imperative for nurses to possess sufficient knowledge regarding management of traumatic dental injuries.
Keywords: dental trauma; avulsion; nurses; knowledge